Fundamentals of Biomechanics - O ¨ zkaya, Nihat; Goldsheyder, David; Nordin, Margareta (Springer, 2018)
Biomechanics is an exciting and fascinating specialty with the goal of better understanding the musculoskeletal system to enable the development of methods to prevent problems or to improve treatment of patients. Biomechanics has increasingly become an interdisciplinary field where engineers, physicists, computer scientists, biologists, and material scientists work together to support physicians, sports scientists, ergonomists, and physiotherapists and many other professionals. This book Fundamentals of Biomechanics summarizes the basics of mechanics, both static and dynamics including kinematics and kinetics. The book introduces vectors and moments, applying them with many simple examples, which are essential to determine quantitatively or at least estimate loads acting during different situations or exercises on bones and joints. Joints and bones are mostly stabilized by their associated ligaments and muscles and therefore such calculations also require knowledge of the complex anatomy. Creativity is also needed to simplify these often complicated scenarios to reduce the parameters for the free body diagrams that can be used to develop the equations that can be solved. This book presents the concepts and explains in detail examples for the elbow, the shoulder, the spinal column, the neck, the lumbar spine, the hip and the knee, as well as the ankle joint. The reader however should also be aware that results from such calculations should be validated with available in vivo studies because muscle forces are often not known and the simplifications may be too strong.
Equilibrium, Motion, and Deformation